Das Paradigma deutscher Modalpartikeln : Dialoggrammatische Funktion und paradigmeninterne Oppositionen. - Brünjes, Lena (Reihe Germanistische Linguistik., 2014)
Are modal particles grammatical signs? This study investigates whether the modal particle meets the two key criteria forclassifying itas a grammatical element. Do all modal particles have a relational function? And do they constitute a grammatical paradigm? Describing this paradigm lends insight into the distribution and significance of specific particles and the internal structure of this part of speech.